Further evidence of response by leukaemia patients in remission to antigen(s) related to acute myelogenous leukaemia. - Cocks, P. (Nature Publishing Group, 1977)
Fifteen patients with acute myelogenous leukaemia were studied to determine if their remission blood leucocytes could be stimulated into taking up [3H] thymidine after in vitro culture with their own cryo-preserved irradiated AML leukaemia cells. In 6/15 patients it was possible to show autologous recognition and equal recognition of their stored leukaemia cells, even when they had previously been maintained in in vitro proliferative cultures in liquid suspension and undergoing myeloid maturation for one week. After in vitro proliferative culture, 4 populations of leukaemia cells produced material in the supernatant media between 3 and 7 days capable of inducing [3H] thymidine uptake in autologous (2 pts, 5 supernatants) and allogeneic (2 pts, 2 supernatants) AML remission lymphocytes, but not in normal donor lymphocytes. The relevance of these observations to tumour-associated AML antigen is discussed.